Induction of the phage resistance in the progeny of an infected bacterial cell - Pererva, T.P. (Биополимеры и клетка, 1999)
Using bacteriophages MS2, P17 and λ-vir infecting Escherichia call AB 259 (Hfr 3000), E. coli MIT and E. coli C600 cells appropriately the author demonstrates that both RNA- and DNA-containing piiages induce the development of phase-resistant forms appearing with high frequency in the progeny of infected cells. На моделях бактеріофагів MS2, Р17 та λ-vir, що інфікують Escherichia coli АВ 259 (Hfr 3000), Е. coli М17 та Е. coli С600 відповідно, показано, що за умов уповільненого розвитку інфекції як РНК-, так і ДНК-вмісні бактеріофаги спричиняють появу високого відсотка фагостійких форм у клітинному потомстві. С использованием бактериофагов MS2, Р17 и λ-vir, инфицирующих Escherichia coli АВ 259 (Hfr 3000), Е. coli M17 и E. coli C600 соответственно, показано, что в условиях замедленного развития инфещии как РНК-, так и ДНК-содержащие бактериофаги индуцируют появление высокого процента фигирмистентных форм в клеточном потомстве.